Community Service: Developing Web-Based Interactive Digital Books to Improve Learning Outcomes at MIN 2 Palangka Raya - Arif Dian Pratama; Rahmat Rahmat; Zaitun Qamariah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This collaborative community service activity aims to improve the learning outcomes of grade IV students at MIN 2 Palangka Raya City using web-based interactive digital books developed by PGMI IAIN Palangka Raya students. This activity is carried out collaboratively, where students design learning media with the guidance of lecturers who also act as expert validators. The activity stage begins with the identification of needs through observations and interviews at partner schools, especially on the theme